Two Photon Fluorescence Microscopy of the Unstained Human Cochlea Reveals Organ of Corti Cytoarchitecture - Iyer, Janani S.; Seist, Richard; Moon, In Seok; Stankovic, Konstantina M. (Frontiers in Cellular Neuroscience, 2021)
Sensorineural hearing loss (SNHL) is the most common sensory deficit worldwide, and it typically originates from the cochlea. Methods to visualize intracochlear cells in living people are currently lacking, limiting not only diagnostics but also therapies for SNHL. Two-photon fluorescence microscopy (TPFM) is a high-resolution optical imaging technique. Here we demonstrate that TPFM enables visualization of sensory cells and auditory nerve fibers in an unstained, non-decalcified adult human cochlea.